Selective laser sintered mould for orbital cavity reconstruction. Issue 1 (3rd January 2019) - Mandolini, Marco; Brunzini, Agnese; Germani, Michele; Manieri, Steve; Mazzoli, Alida; Pagnoni, Mario
Abstract : Purpose: Orbital fractures are the most commonly encountered midfacial fractures, and usually, the fracture involves the floor and/or the medial wall of the orbit. This paper aims to present an innovative approach for primary and secondary reconstructions of fractured orbital walls through the use of computer-assisted techniques and additive manufacturing. Design/methodology/approach: First, through the 3D anatomical modelling, the geometry of the implant is shaped to fill the orbital defect and recover the facial symmetry. Subsequently, starting from the modelled implant, a customised mould is designed taking into account medical and technological requirements. Findings: The selective laser sintered mould is able to model and form several kind of prosthetic materials (e.g. titanium meshes and demineralised bone tissue), resulting in customised implants and allowing accurate orbital cavity reconstructions. The case study proved that this procedure, at the same time, reduces the morbidity on the patients, the duration of surgery and the related costs. Originality/value: This innovative approach has great potential, as it is an easy and in-office procedure, and it offers several advantages over other existing methods.